Efficacy and Safety of Pregabalin in the Treatment of Patients With Painful Diabetic Peripheral Neuropathy and Pain on Walking. Issue 11 (November 2015) - Huffman, Cynthia; Stacey, Brett R.; Tuchman, Michael; Burbridge, Claire; Li, Chunming; Parsons, Bruce; Pauer, Lynne; Scavone, Joseph M.; Behar, Regina; Yurkewicz, Lorraine
Abstract : Objectives: This randomized, double-blind, placebo-controlled, multicenter, 2-period crossover study (two 6-week treatment periods separated by a 2-week washout period) evaluated the efficacy and safety of pregabalin (150 to 300 mg/d) for treatment of pain and pain on walking in patients with painful diabetic peripheral neuropathy (DPN) who experienced pain while walking. Methods: Co-primary efficacy endpoints were: (1) mean pain score (last 7 daily pain diary scores, 0 to 10 numeric rating scale at end of each treatment period) and (2) DPN pain on walking (0 to 10 numeric rating scale immediately after walking 50 feet [15.2 m] on flat surface). Secondary endpoints included other pain parameters, patient-reported sleep, health-related quality of life, and safety measures. Results: Two hundred three patients were treated (pregabalin, n=198; placebo, n=186), with no statistically significant treatment difference for pregabalin versus placebo in the co-primary efficacy endpoints, mean DPN pain ( P =0.0656) and mean DPN pain on walking ( P =0.412). A carryover effect was observed. Analysis of co-primary endpoints for period 1 showed significant treatment difference for DPN pain ( P =0.034) and DPN pain on walking ( P =0.001). Treatment with pregabalin resulted in significant improvements versus placebo on prespecified patient global impression of change (end of period 1; P =0.002), and sleep interference rating scale (end of period 2; P =0.011). Adverse events were more frequent with pregabalin than with placebo and caused discontinuation in 13 (6.6%) pregabalin patients versus 5 (2.7%) placebo patients. Discussion: Failure to meet the co-primary objectives may be related to carryover effect from period 1 to period 2, lower pregabalin dose (150 to 300 mg/d), and/or placebo response in painful DPN. Abstract : Supplemental Digital Content is available in the text.